Model Pendidikan Islam dalam Membangun Toleransi Antar Umat Beragama di Yordania: Tinjauan Terhadap Kebijakan Negara dan Peran Institusi Keagamaan - Kandiri, Kandiri; Hosaini, Hosaini; Rif'ah , Rif'ah; Muzammil, Muzammil (Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to examine the model of Islamic education in building interfaith tolerance in Jordan, with a focus on state policy and the role of religious institutions. Jordan is known as a country that has succeeded in displaying the face of moderate Islam and becoming an example of the practice of religious tolerance in the Middle East region. The approach used in this study is Systematic Literature Review (SLR) on 21 relevant scientific articles, both national and international, published in the last ten years. Data were collected through the stages of identification, selection, analysis, and synthesis of literature. The results of the study indicate that the Islamic education model in Jordan is built on the principle of moderate(moderate), interfaith dialogue, and integration of tolerance values ​​in the religious education curriculum. The Jordanian government actively formulates national policies that support religious moderation, such as through the national curriculum, training of religious teachers, and capacity building programs for Islamic educational institutions. On the other hand, religious institutions such as the Ministry of Awqaf and the Islamic University of Jordan play an important role in disseminating the values ​​of tolerance and curbing extremism through lectures, sermons, and scientific publications. The discussion underlines the importance of synergy between the state and religious institutions in internalizing the values ​​of tolerance from primary education to higher education. The conclusion of this study confirms that the model of Islamic education in Jordan can be used as a reference in building a peaceful and inclusive multicultural society through a systemic policy approach and an active religious role.